Optimizing Interactive Infographics: A Needs Study for The Development of Begrüßung Materials in German Language Teaching at SMAN 14 Palembang - Krisnatalety, Krisnatalety; Raharjo, Makmum; Susanti, LR. Retno (FKIP - Universitas Riau, 2025)
This study aims to develop interactive infographic-based learning media to enhance the effectiveness of German language teaching, particularly for the Begrüßung material at SMAN 14 Palembang. The research utilized a descriptive qualitative method to analyze the needs of both students and teachers through questionnaires, classroom observations, and interviews. The results show that the majority of students (63%) and teachers (79%) perceive a high need for the development of interactive learning media, particularly infographics that support engagement and material comprehension. Data from the learner needs analysis revealed that 63% of students are in the